THE EFFECT OF RESISTANCE TRAINING ON TRABECULAR BONE SCORE - Lia Arista Wijaya; Clarin Hayes; Indira Juhanna; Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
Osteoporosis is one of the many signs of aging. Physical activities has been known as the best non-pharmacology treatment for osteoporosis as resistance training can stimulate and maintain bone gain. Bone mineral density (BMD) is usually used as the parameter to evaluate bone quality since BMD is used for osteoporosis diagnosis. But, trabecular bone score (TBS) is a far more superior parameter in evaluating bone quality. Regrettably, there is a scarcity of research on this topic, as the majority of studies utilize BMD as the parameter for assessing bone quality. This literature review aims to provide data about the effect of resistance training on TBS for better early prediction and prevention of morbidity and mortality caused by osteoporosis-related fractures. The study searches for articles published in the last 10 years in English or French discussing resistance training and TBS. Five studies are included, which consist of 3 experimental studies and 2 case-control studies. The results suggest that resistance training can stimulate and maintain bone gain, which is superior to non-weight-bearing exercise. TBS has been found to be a more accurate predictor of fracture risk compared to BMD alone. Overall, the literature review suggests that resistance training may improve TBS and prevent osteoporosis-related fractures. Based on Frost's mechanostat theory, bone mechanical properties can be significantly enhanced through high strain generated during physical activity. Nevertheless, the bone's adaptive response to resistance exercise is typically specific to the trained site, which means that only the region exercised will exhibit greater bone mineral density.